2015
DOI: 10.1002/anie.201500220
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)‐Catalyzed Regiospecific Dimerization of Aromatic Acids: Two Direct CH Bond Activations in Water

Abstract: 2,2'-Diaryl acids are key building blocks for some of the most important and high-performance polymers such as polyesters and polyamides (imides), as well as structural motifs of MOFs (metal-organic frameworks) and biological compounds. In this study, a direct, regiospecific and practical dimerization of simple aromatic acids to generate 2,2'-diaryl acids has been discovered, which proceeds through two rhodium-catalyzed C-H activations in water. This reaction can be easily scaled up to gram level by using only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
46
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 69 publications
0
46
0
4
Order By: Relevance
“…In recent years,s ubstantial advances in carboxylate-directed CÀHa ctivation have been made, [13] for example,b yt he groups of Yu, [14] Miura, [15] Ackermann, [16] and Larrosa, [12b,c] as well as our own group. [12d, 17] In this context, oxidative couplings of benzoic acids with alkynes to form isocoumarins,naphthalenes,and other cyclic structures have intensively been studied.…”
mentioning
confidence: 99%
“…In recent years,s ubstantial advances in carboxylate-directed CÀHa ctivation have been made, [13] for example,b yt he groups of Yu, [14] Miura, [15] Ackermann, [16] and Larrosa, [12b,c] as well as our own group. [12d, 17] In this context, oxidative couplings of benzoic acids with alkynes to form isocoumarins,naphthalenes,and other cyclic structures have intensively been studied.…”
mentioning
confidence: 99%
“…[1] Thec arboxy group,o ne of the most celebrated chelating groups,h as proven to be highly effective for assisting proximity-driven ortho-C(sp 2 )ÀHbond metalation of benzoic acids with metals such as Pd, Ru, Rh, and Ir through k 1 coordination, [2] and was pioneered by the groups of Miura and Satoh, [3a,e,f] Yu,[3c] Daugulis, [3d,p] Ackermann, [3h] Larrosa, [3j] as well as Gooßen [3m] and others (Scheme 1a). [3][4][5][6] Thei mportance of k 1 coordination of the carboxy group in promoting ortho-CÀHactivation of benzoic acids has been accounted for by Yu and co-workers,who also devised asuccessful means of shifting the equilibrium from the preferred k 2 to k 1 coordination to the Pd center by utilizing as uitable countercation such as either Na + or NR 4 + . [1d] The k 2 coordination is considered not effective for promoting the cyclometallation with ortho-C(sp 2 )ÀHb onds because of its unsuitable geometry.H owever,w eh ypothesize that this unexplored k 2 coordination mode for C(sp 2 )ÀHa ctivation can be used for delivering am etal catalyst such as Pd to recognize ar emote C À Hb ond for geometry-driven C À Ht ransformations,w hile leaving the C À Hb ond proximal to the carboxy group intact, since the carboxylate-coordinated Pd II complex prefers to adopt the k 2 coordination in the absence of ac ountercation (Scheme 1b).…”
mentioning
confidence: 99%
“…First, oxidant re-evaluation demonstrated that both AgOAc and Ag 2 CO 3 were viable oxidants but they would result in minor decarboxylation of the carboxy DG in the olefinated products;AgOPiv did not lead to decarboxylation and was therefore the optimal oxidant (Table 1, entries [5][6][7][8].…”
mentioning
confidence: 99%
“…[1] Initially, this approach was often limited by the use of complex directing groups, [2] which needed to be installed and later removed, thus adding steps to the overall process.Instate-ofthe-art methods,t he selectivity can be enforced even by ubiquitous functionalities,i ncluding ketone, [3] hydroxy, [4] or carboxylate groups. [6] Inspired by pioneering work by Miura and co-workers, [7] ah uge variety of carboxylatedirected sp 2 CÀH ortho-functionalizations have been developed for example,b yt he groups of Yu, [8] Li, [9] Daugulis, [10] Larrosa, [11] Ackermann, [12] Su, [13] Baidya, [14] our group, [15] and others. [6] Inspired by pioneering work by Miura and co-workers, [7] ah uge variety of carboxylatedirected sp 2 CÀH ortho-functionalizations have been developed for example,b yt he groups of Yu, [8] Li, [9] Daugulis, [10] Larrosa, [11] Ackermann, [12] Su, [13] Baidya, [14] our group, [15] and others.…”
mentioning
confidence: 99%